Anatomy of a Transcatheter Mitral Valve Service - Gill, Harminder; Adams, Heath S. L.; Chehab, Omar; Allen, Christopher; Hancock, Jane; Lamata, Pablo; Lucchese, Gianluca; Prendergast, Bernard; Redwood, Simon; Patterson, Tiffany; Rajani, Ronak (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter mitral therapies offer treatment options to selected patients who are unable to undergo open procedures due to prohibitive surgical risk. Data detailing the design and structure of transcatheter mitral services to ensure appropriate patient selection and tailored management strategies is lacking. We report our initial experience of developing and running a purpose-built transcatheter mitral service. The nature and number of referral sources, the multi-disciplinary make-up of the dedicated Mitral Heart Team and the use of integrative imaging assessment with incorporation of computational solutions are discussed. In addition, a summary of the clinical decision-making process is presented. This report sets out a framework from which future clinics can evolve to improve and streamline the delivery of transcatheter mitral therapies.